Exploring the holistic well-being of teachers: a preliminary investigation of a key professional group in South India - M. R., Mythily; M., Vinay; B. R., Harish; Upadhya, Kavya G.; Singh, Sunitha (International Journal Of Community Medicine And Public Health, 2025)
Introduction: There are many factors with respect to occupation of teachers which can negatively impact teachers’ physical, mental and social wellbeing. Stressful working conditions for teachers have increasingly become a problem in many countries. The present study is taken up to assess their physical, mental and social dimensions of health. Methodology: It was a cross-sectional study conducted among 552 school teachers, selected by simple random sampling method. The data was entered in Microsoft excel software and analysed using SPSS software (trial version). Descriptive and inferential statistical tests were used. P value <0.05 was considered significant. Results: Among the 552 study participants 271 (49.1%) were male teachers and 281 (50.9%) were female teachers. Majority 251 (45.5%) belonged to age group of 41-50 years followed by 155 (28.1%) belonged to age group of 51-60. The mean BMI of the study population was 26.25±3.97 kg/m2. The mean BMI of males was 25.77±3.88 kg/m2 and females was 26.71±4.27 kg/m2. Mean Mental Health Inventory score of males was 67.88±8.91 which was higher compared to mean score of females 65.82±9.20 and the difference was statistically significant. Majority 504 (91.3%) had “good social well-being”, 44 (8.0%) had “better social well-being” and 4 (0.7%) had “poor social well-being”. Conclusion: Teachers physical health was more compromised compared to general population. Mental health and social well-being were good among teachers. More studies are warranted to explore the health problems of teachers.